2021
DOI: 10.1038/s41598-021-99780-1
|View full text |Cite
|
Sign up to set email alerts
|

Robust skyrmion mediated reversal of ferromagnetic nanodots of 20 nm lateral dimension with high Ms and observable DMI

Abstract: Implementation of skyrmion based energy efficient and high-density data storage devices requires aggressive scaling of skyrmion size. Ferrimagnetic materials are considered to be a suitable platform for this purpose due to their low saturation magnetization (i.e. smaller stray field). However, this method of lowering the saturation magnetization and scaling the lateral size of skyrmions is only applicable where the skyrmions have a smaller lateral dimension compared to the hosting film. Here, we show by perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Such a physical RC paradigm can be well suited to learning relatively simple tasks in-situ on edge devices where energy and hardware resources are severely constrained. In future, for scaling the proposed skyrmion based reservoir, 2D magnetic materials can be used since it has been recently demonstrated that DMI increases when magnetic materials have a small thickness or monolayer as 2D magnetic materials [49], and high DMI is necessary for scaling skyrmions [23,24,50,51]. Therefore, 2D magnetic materials based straintronic PRC can be a fascinating topic to further investigate in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a physical RC paradigm can be well suited to learning relatively simple tasks in-situ on edge devices where energy and hardware resources are severely constrained. In future, for scaling the proposed skyrmion based reservoir, 2D magnetic materials can be used since it has been recently demonstrated that DMI increases when magnetic materials have a small thickness or monolayer as 2D magnetic materials [49], and high DMI is necessary for scaling skyrmions [23,24,50,51]. Therefore, 2D magnetic materials based straintronic PRC can be a fascinating topic to further investigate in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of very small depinning current compared to domain walls in racetrack memory devices [11,[15][16][17] and their scalability have made skyrmions a potential candidate for high density and low power spintronic devices [18][19][20]. For example, our group has shown the feasibility of voltage control of skyrmions [21] and that skyrmion mediated voltage-controlled memory devices [22] can be scaled aggressively [23,24]. Similarly, skyrmion can be a viable option for low-power, small-scale reservoir devices [1,25].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the stability of skyrmions at room temperature has been demonstrated in thin films and in confined geometries, like ferromagnetic stripes and nanodots [13][14][15][16][17] . Often, in spite of the topological protection, the skyrmion configuration is not self-nucleating and is not ground state [18][19][20] . Therefore, an important question arises whether the right selection of materials and nano-structuralization or environmental conditions can improve the skyrmion stability and provide effective functionality for applications.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic skyrmions have intriguing features such as inherent topological protection, nanoscale dimension (ranging from the 100 nm to the 1 nm) [19][20][21], high operating speed [21][22][23], and low-driving current density [24]. Because of these characteristics, skyrmions are the promising candidates for developing highly energy-efficient and ultra-dense integrated nanodevices.…”
Section: Introductionmentioning
confidence: 99%